2017
DOI: 10.1093/jb/mvx012
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of metagenomic β-xylosidase/ α-l-arabinofuranosidase activated by calcium

Abstract: The crystal structure of metagenomic β-xylosidase/α-l-arabinofuranosidase CoXyl43, activated by calcium ions, was determined in its apo and complexed forms with xylotriose or l-arabinose in the presence and absence of calcium. The presence of calcium ions dramatically increases the kcat of CoXyl43 for p-nitrophenyl β-d-xylopyranoside and reduces the Michaelis constant for p-nitrophenyl α-l-arabinofuranoside. CoXyl43 consists of a single catalytic domain comprised of a five-bladed β-propeller. In the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 25 publications
5
15
0
Order By: Relevance
“…Fig 4C ) or arabinose (Xyl•arabinose•xylose structure; Fig 1B ) are present. This observation is in contrast with the structure of the type I GH43 β-xylosidase/α- L -arabinofuranosidase CoXyl43, in which a xylose molecule was found in subsite -1 of the enzyme [ 36 ].…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…Fig 4C ) or arabinose (Xyl•arabinose•xylose structure; Fig 1B ) are present. This observation is in contrast with the structure of the type I GH43 β-xylosidase/α- L -arabinofuranosidase CoXyl43, in which a xylose molecule was found in subsite -1 of the enzyme [ 36 ].…”
Section: Resultsmentioning
confidence: 64%
“…This result differs from kinetic studies with S . ruminantium β-1,4-xylosidase [ 11 , 22 ] and structural studies with a metagenomic β-xylosidase/α- L -arabinofuranosidase CoXyl43 [ 36 ], a type I GH43 enzyme, which suggested that arabinose could bind to both subsites -1 and +1.…”
Section: Resultsmentioning
confidence: 99%
“…The parameters related to structure flexibility of Xyn10A, Xyn11A and Xyl43A and their structure-resolved counterparts were analyzed and shown in Table 7 . The GH10 xylanase of Thermoascus aurantiacus ( Ta Xyn10) 53 , 54 and GH11 xylanase of Thermomyces lanuginosus ( Tl Xyn11) 55 are thermophilic, while the GH43 xylosidase-arabinofuranosidase from a compost metagenome (CoXyl43) 56 , 57 is mesophilic. Their structure elements, protein interaction and accessible surface area were compared to reveal the cold-adapted strategies.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme flexibility is characterized by decreased contents of Arg and Pro reduced interactions, and increased Gly content, Gly/Pro ratio, hydrophobic accessible area 9 11 , 76 . To identify the cold-active catalytic mechanism of the xylanolytic enzyme system of C. neopsychrotolerans SL-16, three thermophilic or mesophilic counterparts Ta Xyn10 53 , 54 , Tl Xyn11 55 , and CoXyl43 56 , 57 were selected for comparison of some structural features (Table 7 ). Of the three xylanolytic enzymes, only Xyn10A followed the cold-adapted strategy that high Gly content, increased Gly/Pro ratio and surface hydrophobicity, and less Arg and Pro contribute to enzyme flexibility 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation